Model Pembelajaran dalam Mengembangkan Multiple Intelligences Pada Anak Usia Dini (PIAUD IAIN Kudus, 2018)
Learning method can be interpreted as a way used to implement the plan that has been prepared in the form of real and practical activities to achieve learning objectives. There are several learning methods that can be used to implement learning strategies. Learning model has a broader meaning than the strategy, method or procedure of learning.Multiple intelligences differentiates intelligence into specific 'modalities', rather than seeing intelligence as dominated by a single general ability. Howard Gardner proposed this model in his 1983 book Frames of Mind: The Theory of Multiple Intelligences. According to Gardner, an intelligence must fulfill eight criteria: potential for brain isolation by brain damage, place in evolutionary history, presence of core operations, susceptibility to encoding (symbolic expression), a distinct developmental progression, the existence of savants, prodigies and other exceptional people, and support from experimental psychology and psychometric findings.